2014
DOI: 10.1186/1471-2466-14-68
|View full text |Cite
|
Sign up to set email alerts
|

Soluble receptor for advanced glycation end-products and progression of airway disease

Abstract: BackgroundThe receptor for advanced glycation end-products (RAGE) is highly expressed in the lung, where it is believed to have a homeostatic role. Reduced plasma levels of soluble RAGE (sRAGE) have been reported in patients with chronic obstructive pulmonary disease (COPD). The aim of the present study was to evaluate the association of plasma sRAGE levels with a longitudinal decline of lung function. We have also measured plasma levels of high mobility group box 1 (HMGB1), a RAGE ligand which has been associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 28 publications
5
52
1
Order By: Relevance
“…Similarly, we did not observe a correlation between decreased lung function and serum or sputum levels of sRAGE ( fig. 1k), as previously reported [14][15][16].…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Similarly, we did not observe a correlation between decreased lung function and serum or sputum levels of sRAGE ( fig. 1k), as previously reported [14][15][16].…”
supporting
confidence: 58%
“…Therefore, it will be of interest to further elucidate the role of RAGE in exacerbations of COPD. Multiple studies have shown that sRAGE is decreased in serum or plasma of COPD patients, which may act to further potentiate the effect of RAGE ligands [9,[14][15][16]. However, in our study, induced sputum and serum levels of sRAGE did not differ between stable disease and exacerbation (sputum levels 159.5±18.7 and 164.0±21.5 pg·mL −1 , respectively) ( fig.…”
contrasting
confidence: 48%
“…The participants were part of a longitudinal study, of a cohort of smokers and nonsmokers, being conducted in northern Finland. The details of the project and the inclusion and exclusion criteria have been previously published (16,20,34,35). In brief, the exclusion criteria consisted of chronic pulmonary or other diseases requiring regular medication, allergies, and risk factors for other pulmonary diseases, e.g., known exposures, bronchiectasis, malignancies, and also previous lung tuberculosis.…”
Section: Methodsmentioning
confidence: 99%
“…In recent proteomic studies from our laboratory the major findings included an elevation of surfactant protein-A (SP-A) and a decrease of specific variants of the receptor for advanced glycation end products (RAGE) in lung tissue (25,26) and polymeric immunoglobulin receptor in sputum samples from patients with COPD (24). Of these, SP-A and soluble RAGE have been validated in longitudinal approaches in larger cohorts (16,20). Our previous proteomics study also identified elevated levels of bactericidal/permeability-increasing protein fold containing protein B1 (BPIFB1, formerly known as LPLUNC1) in induced sputum from smokers and patients with COPD compared with nonsmokers (24).…”
mentioning
confidence: 99%
“…Soluble receptor for advanced glycation end products (sRAGE) consists of the extracellular domain but lacks the trans-membrane and cytoplasmic domains of RAGE in human plasma (9). sRAGE may have an inflammatory or homeostatic role to play in lung tissue (5,10), and is studied as an effective biomarker in ARDS (8,10), ALI (8,10), lung cancer (11) and chronic obstructive pulmonary disease (12).…”
Section: Introductionmentioning
confidence: 99%